2020
DOI: 10.3389/fimmu.2020.01902
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Mycobacterium tuberculosis Promotes Both M1/M2 Polarization and MMP Production in Cigarette Smoke-Exposed Macrophages

Abstract: Pulmonary tuberculosis (PTB) is a risk factor for COPD. Our previous study revealed more severe emphysema in COPD patients (mostly smokers) with prior tuberculosis. However, the mechanisms of interactions between cigarette smoke (CS) and Mycobacterium tuberculosis (Mtb) are unknown. In this study, we found that the frequencies of both M1 and M2 macrophages, and levels of MMP9 and MMP12 in bronchoalveolar lavage were increased in PTB patients with smoking. Between-group analysis showed that the frequency of M1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
1
36
0
2
Order By: Relevance
“… 28 , 37 A growing body of evidence indicates that M2 macrophages can secrete MMP9 and MMP12. 38 , 39 However, the relationship between macrophage polarization and MMPs production is complex and remains controversial. Macrophages can be polarized in one of two directions.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 37 A growing body of evidence indicates that M2 macrophages can secrete MMP9 and MMP12. 38 , 39 However, the relationship between macrophage polarization and MMPs production is complex and remains controversial. Macrophages can be polarized in one of two directions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings also showed that the levels of MMP9 and MMP12 in bronchoalveolar lavage were increased in PTB patients who smoked. Between-group analysis showed that the frequency of M1 macrophages was higher in non-smoker PTB patients, while more M2 macrophages were found in smokers without PTB than in nonsmokers [125].…”
Section: Tuberculosis (Tb)mentioning
confidence: 88%
“…In our study, a substantial switch to the M2 phenotype at a later stage (72h) was observed in uninfected control macrophages compared to infected AMs, which could be due to increased expression of MMPs in control cultures. Upregulation of certain MMPs was found to be associated with macrophage polarization to both M1 and M2 phenotypes in M.tb -infected, cigarette smoke-exposed macrophages(Le et al, 2020).…”
Section: Discussionmentioning
confidence: 99%